(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Tooth loss is a common dental condition with great potential to negatively affect an individual's QoL and psychosocial wellbeing. In Arab world, dental caries, periodontal disease and trauma are the top causes of tooth loss that leads to the humiliation and social disengagement. Although we have done a lot with our dental treatments like implants, the awareness level is still low for the public. The purpose of this study was to assess knowledge and attitude towards use of treatment options for tooth defected and loss by Saudi population, as well as to evaluate psychosocial effects related to those disorders. Methods: A descriptive cross-sectional study was carried out in Saudi Arabia between July - November 2024 using online questionnaires. Residents aged 18 and older but excluding those with formal dental education were the participants. We collected demographic data as well as measured participants' awareness of treatment options and psychosocial effects of tooth loss. Results: This study included 903 participants, mean age of the participants 30.2 years and 63.7% females are total of 903 participants. The results showed that 75.9 percent of respondents have tooth decay and 49.9 percent feared more ill dental conditions. Notably, difficulties eating or a loss in self-esteem due to their dental problem was reported by 42.3% and 28.3% respectively. Although there was high recognition of basic treatments, concerning 75.2% of participants were ignorant of advanced treatment options. The 65.5% preferred dental implants with missing teeth. Significant relationships between knowledge levels and age (p=0.001) and occupational status (p=0.0001) were found as a result of the statistical analysis. Conclusion: The study identifies a significant knowledge gap regarding dental treatment choices and the psychological consequences of tooth loss in the Saudi population. These findings highlight the compelling need for tailored educational initiatives to raise awareness and encourage the adoption of healthy dental practices while also improving the quality of life and self-esteem of people with dental abnormalities.